2004
DOI: 10.1073/pnas.0403857102
|View full text |Cite
|
Sign up to set email alerts
|

Populations of photoinactivated photosystem II reaction centers characterized by chlorophyllafluorescence lifetimein vivo

Abstract: O xygenic photosynthetic organisms grow under an everchanging sunlight environment. Fluctuations of solar energy input can be accommodated by a tradeoff between energy utilization in photosynthetic carbon assimilation and energy dissipation by various photoprotective mechanisms that modulate absorption and dissipation of excess light energy (1-3). Despite the complex suite of strategies for photoprotection, however, photooxidative damage inevitably occurs to photosystem (PS) II, in which P680 ϩ (a special Chl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 46 publications
2
112
0
2
Order By: Relevance
“…It has been shown that some of these PSII centers are inactive in electron transport and may function as an additional antenna to the fraction of active PSII centers (Terao and Katoh, 1996). Recently, Matsubara and Chow (2004) have suggested that un-active (or photoinhibited) centers of PSII can receive energy from neighboring functional PSII reaction centers and subsequently dissipates this energy nonphotochemically via non-radiative charge recombination between Q A -and P680 + . We suggest that such a mechanism would provide effective photoprotection of the remaining functional PSII units, although the possibility for reaction center quenching in active PSII centers can not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that some of these PSII centers are inactive in electron transport and may function as an additional antenna to the fraction of active PSII centers (Terao and Katoh, 1996). Recently, Matsubara and Chow (2004) have suggested that un-active (or photoinhibited) centers of PSII can receive energy from neighboring functional PSII reaction centers and subsequently dissipates this energy nonphotochemically via non-radiative charge recombination between Q A -and P680 + . We suggest that such a mechanism would provide effective photoprotection of the remaining functional PSII units, although the possibility for reaction center quenching in active PSII centers can not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The second is the photoprotective capacity associated with these photoinactivated PSII reaction centres and regulation of the D1 repair cycle [62]. Matsubara & Chow [63] demonstrated that these inactive centres are highly dissipative. This component of NPQ PI , with its particularly slow relaxation in the dark, seems to persist for one to two weeks in avocado leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there are photoacclimatory mechanisms that involve photochemical quenching, only photoacclimation involving an upregulation of non-photochemical quenching, such as the accumulation of inactive PSII (a population of PSII that engage solely in mitigating excess excitation energy via heat dissipation), will reduce F v /F m [51]. The rate of inactive PSII accumulation and the consequent reduction in F v /F m is proportional to the light absorbed in excess by the photosynthetic membranes of the algae [52]. According to this physiological background, two main parameters need to be generated to quantify photodamage: the first describes the amount of excess solar energy absorbed by a symbiont that significantly contributes to increased rates of PSII photoinactivation, called Excess Excitation Energy (EEE, mol quanta m −2 day −1 ); and the second is the amount of photodamage accumulated (i.e., inactive PSII).…”
Section: Coral Response To Variable Solar Irradiancementioning
confidence: 99%